Damage Detection Using Measurement Response Data of Beam Structure Subject to a Moving Mass - Lee,Eun-Taik (2015)
Abstract The moving load problem is divided into two typical types: moving force and moving mass. The moving mass problem includes the time-varying mass effect. This work considers damage detection of the beam structure subject to a moving load including the inertia effect based on the only measurement data from strain gages and accelerometers without any baseline data. This experiment compares the feasibility of damage detection methods depending on the measurement sensors of strain gages and accelerometers. The measurement data are transformed to the proper orthogonal modes (POMs) in the time domain and the frequency domain, respectively. The magnitude of the moving mass and its velocity are also evaluated as test variables in this experiment. It is shown in the beam tests that the measured strain data can be more explicitly utilized in detecting damage than the acceleration data, and the mass magnitude and its velocity affect the feasibility of damage detection.